2017
DOI: 10.1002/celc.201700069
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Aqueous n‐Octanoate Electrolysis with Electrolytic Conductivity Collapse Caused by the Formation of n‐Octanoic Acid/n‐Octanoate Agglomerates

Abstract: Electroorganic synthesis performed in water (as a green solvent) bears potential for the selective production of chemicals from renewable power. Yet, the limited solubility of organic molecules hampers their aqueous electrolysis. For the proposed platform chemical n-octanoic acid/n-octanoate, both summarized as C 8 , it is shown that the aqueous electrolysis of C 8 can be performed successfully, provided that certain requirements are fulfilled. It is evidenced that the often-overlooked local pH shift in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…For the latter, we previously demonstrated that Na 2 SO 4 , as supporting electrolyte different to KNO 3 , has no effect on the CE of the Kolbe electrolysis of n ‐valeric acid, but a higher a concentration of Na 2 SO 4 increases the rate of acid degradation [14] . Additionally, we also proved that due to local pH shifts n ‐octanoic acid/ n ‐octanoate forms agglomerates in aqueous solutions during Kolbe electrolysis, leading to a deterioration of the electrolysis [15] . In summary, supporting electrolyte species and concentration, pH, as well as the nature of the MCCA have an influence on the Kolbe electrolysis performance and therefore have to be well balanced.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…For the latter, we previously demonstrated that Na 2 SO 4 , as supporting electrolyte different to KNO 3 , has no effect on the CE of the Kolbe electrolysis of n ‐valeric acid, but a higher a concentration of Na 2 SO 4 increases the rate of acid degradation [14] . Additionally, we also proved that due to local pH shifts n ‐octanoic acid/ n ‐octanoate forms agglomerates in aqueous solutions during Kolbe electrolysis, leading to a deterioration of the electrolysis [15] . In summary, supporting electrolyte species and concentration, pH, as well as the nature of the MCCA have an influence on the Kolbe electrolysis performance and therefore have to be well balanced.…”
Section: Introductionmentioning
confidence: 56%
“… [14] Additionally, we also proved that due to local pH shifts n ‐octanoic acid/ n ‐octanoate forms agglomerates in aqueous solutions during Kolbe electrolysis, leading to a deterioration of the electrolysis. [15] In summary, supporting electrolyte species and concentration, pH, as well as the nature of the MCCA have an influence on the Kolbe electrolysis performance and therefore have to be well balanced. Concerning the electrode material most work was performed using (monolithic) pure platinum (Pt).…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by several reasons: (1) the anolyte is salt-rich and not pure water; (2) other carboxylates may affect the solubility; and (3) the apparent increase of the pK a due to micelle formation in electrochemical systems, as discussed by Urban and Harnisch. 35 During periods II−IV, we continued phase separation at different conditions with synthetic broth (pH = 5.5), as described in the Supporting Information (Figure 2A−D, Table S8, and Figure S3). At the conditions of ∼10 times higher n-caproic acid concentrations in a synthetic pertraction solution (pH = 9.0) during period VII, we observed considerable increases in the MCCA-oil fluxes and transfer efficiencies, and thus increased phase separation (Figure 2B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The electrolyte concentration in relation to the pH value of the solution on the other hand significantly influenced the reaction outcome. Although Harnisch and co‐workers recently showed an independence of the product composition on the initial pH values, [1c,19] other sources state that Kolbe reactions are preferred to be carried out in neutral to slightly acidic media, while for Non‐Kolbe electrolysis a slightly alkaline environment is preferable [1a,b] . The described reaction performs best, similar to Kolbe couplings, at a pH value of 5.7 with 65 % of product yield, corresponding to a triethylamine concentration of 0.8 M (Table 1, entry 6).…”
Section: Resultsmentioning
confidence: 87%